Contaminants of concern (CoCs) pivotal in assessing the fate of MSW incineration bottom ash (MIBA): First results from India and analogy between several countries. (November 2021) - Gupta, Garima; Datta, Manoj; Ramana, G.V.; Alappat, B.J.; Bishnoi, Shashank
Graphical abstract: Highlights: Characterization of MIBA from 3 MSWI plants in Delhi to assess disposal or reuse. Compilation of 50 studies on MIBA leaching to identify CoCs critical to fate of MIBA. Comparative assessment of CoCs to evaluate variability across countries. Emphasis on mandatory inclusion of the identified CoCs in future studies. Abstract: Present study characterizes municipal solid waste incineration bottom ash (MIBA) from three incineration plants in Delhi with an intent to serve the dual objectives: a) assessing the disposal/reuse options for Delhi MIBA, b) evaluating variability in results across the countries (including India) and assessing if is significant enough to influence the fate of MIBA of varied origin. A review on leaching studies of MIBA (50 research papers) was conducted which aided in achieving both the objectives. Delhi MIBA samples were analysed for chemical composition. The two commonly adopted leaching tests i.e., TCLP and EN 12457–2, were conducted and the results were checked against regulatory threshold levels (RTLs) to achieve the first objective. Leaching concentration of the contaminants was compared with the compiled literature and RTLs to accomplish the second objective. The compendium of literature most importantly revealed the physicochemical parameters which are pivotal in determining the fate of MIBA but have been missing from many studies. Ten such parameters were identified: Cr, Cu, Mo, Sb, Cl -, SO 4 2-, Cd, Pb, Ni and Zn and are referred as contaminants of concern (CoCs). Delhi MIBA was found suitable for disposal to non-hazardous waste landfills and unsuitable for unrestricted reuse. CoCs identified in Delhi MIBA were identical to those observed in literature (except Cd, Pb and Zn). The variability in leaching concentration of CoCs, observed from comparative assessment of results, spanned nearly 2 to 3 log 10 magnitudes for Cu, Cr, Pb, Sb and Zn while 1 to 2 log 10 magnitudes for Mo, Cl - and SO 4 2- .